A STUDY OF COMPOUND PARTICLES IN EMULSION - Ahmad, Tufail (JOURNAL OF ADVANCES IN PHYSICS, 2014)
An attempt is made to study the compound particles by taking black and shower particles together. Average compound particle multiplicity is found to vary linearly with heavily ionizing particle multiplicity but with black particle multiplicity it does not show a linear dependence. Dispersion of the compound multiplicity distribution has also been studied. The ratio of the mean number of compound particles to its dispersion for different target sizes has been calculated.